Heat storage unit, assembly method thereof and heat pump system
By using thickeners and thermal fillers of polysaccharides A and B in inorganic hydrated salt phase change materials, the problem of difficulty in taking into account viscosity and stability is solved, and the efficient heat storage of inorganic salt phase change materials in heat pump systems is achieved. Heat exotherm ensures the stability of the system and heat transfer efficiency.
Patent Information
- Application Number
- CN202411364715.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-27
- Publication Date
- 2025-01-03
AI Technical Summary
Inorganic hydrated salt phase change materials have problems in the heat pump system that are difficult to take into account both the viscosity and component stability, which leads to difficulty in dispersion and inconvenient filling, and high temperatures can easily lead to component failure.
Polysaccharide A and polysaccharide B are used as thickeners, and through appropriate proportions and temperature control, a molten mixture is formed to facilitate filling and maintain stability, combining thermal fillers and nucleating agents to ensure the phase change layer in the heat pump system. stability and heat transfer efficiency.
It realizes good viscosity and stability of inorganic salt phase change materials, ensures effectiveness and efficient heat transfer in heat storage and exothermic processes in heat pump systems, avoids component failure, and is suitable for energy storage applications in heat pump systems.
Smart Images

Figure CN119245411A_ABST
Abstract
Description
Technical Field
[0001] The present application relates to the technical field of energy storage materials, and in particular to a heat storage unit and an assembly method thereof, and a heat pump system. Background Art
[0002] With the deepening of industrialization, the energy gap is becoming more and more obvious. The shortage of primary energy has attracted great attention from people. For this reason, humans have come up with many solutions. Improving energy utilization and developing renewable energy have become important issues.
[0003] Phase change energy storage is a technology that uses phase changes (solid-liquid, gas-liquid) of materials to store energy. The heating process involves two processes: sensible heat storage and latent heat storage. During the latent heat storage process, the material temperature is almost constant. Compared with water that only uses sensible heat to store heat, phase change materials have higher heat storage capacity. Therefore, phase change materials have very high application advantages in heat pump systems. For example, in the temperature range of 10℃ to 65℃, the energy storage density of phase change materials can reach twice that of water, and the volume of the phase change module can be reduced to 50% of that of an independent water tank. In the heat pump system, the phase change material absorbs heat from the heat source during its energy storage process, and the phase change material transfers heat to low-temperature domestic water during its heat release process to achieve instant hot water. The higher the phase change temperature of the phase change material, the higher the outlet water temperature.
[0004] As a type of phase change material, the inorganic hydrated salt system has the advantages of high latent heat of phase change and low cost. However, inorganic hydrated salts have the disadvantage of phase separation. By introducing a thickener to increase the viscosity of the system, the thickener can capture water molecules and prevent them from escaping from the inorganic salt, thereby reducing phase separation. In order to ensure the thickening effect, the thickener concentration in the phase change material system is adjusted to a large level. However, it is easy to agglomerate during the dissolution process and is difficult to disperse evenly. In addition, the viscosity of the phase change material system is large and is not convenient for filling. By increasing the temperature of the system, the viscosity of the phase change material system can be reduced. However, too high a temperature can easily cause the components in the phase change material system to fail. Summary of the invention
[0005] The embodiments of the present application provide a heat storage unit and an assembly method and application thereof, which can solve the problem that it is difficult for a phase change material system to balance viscosity and component stability.
[0006] In a first aspect, an embodiment of the present application provides a heat storage unit for a heat pump system, wherein the heat storage unit comprises a heat storage shell and a phase change layer, wherein the heat storage shell has a heat storage space, and the phase change layer is filled in the heat storage space;
[0007] Wherein, the phase change layer comprises an inorganic salt phase change material, and the inorganic salt phase change material comprises the following components: 90.0wt.% to 95.0wt.% of inorganic hydrated salt A, 1.0wt.% to 5.0wt.% of nucleating agent, 0.5wt.% to 1.5wt.% of thickener, and 1.0wt.% to 3.0wt.% of thermal conductive filler;
[0008] The thickener comprises polysaccharide A and polysaccharide B, wherein the polysaccharide A comprises at least one of linear polysaccharides, and the polysaccharide B comprises at least one of branched polysaccharides;
[0009] Based on the total weight of the thickener, the weight percentage of the polysaccharide A is a, and the weight percentage of the polysaccharide B is b, wherein 2.9≤a / b≤5.5.
[0010] In some embodiments, 75.0 wt. % ≤ a ≤ 84.6 wt. %.
[0011] In some embodiments, the polysaccharide A is selected from at least one of sodium carboxymethyl cellulose, sodium hydroxymethyl cellulose, and hydroxyethyl cellulose;
[0012] The polysaccharide B is selected from at least one of xanthan gum, sodium alginate, pectin and carrageenan.
[0013] In some embodiments, the weight ratio of the inorganic hydrated salt A to the thickener is S, and S satisfies 70.8≤S≤153.3.
[0014] In some embodiments, the inorganic hydrated salt A is selected from at least one of magnesium nitrate hexahydrate, sodium thiosulfate pentahydrate, sodium acetate trihydrate, and calcium chloride hexahydrate;
[0015] The nucleating agent is selected from sodium salts and strontium salts: at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium metasilicate nonahydrate, strontium sulfate, and strontium chloride hexahydrate;
[0016] The thermally conductive filler is selected from at least one of fumed silica, copper foam, expanded graphite, carbon nanotubes, molybdenum disulfide and boron nitride.
[0017] In some embodiments, the thermal storage housing comprises:
[0018] main housing;
[0019] A plurality of heat-conducting fins are arranged in the inner space of the main shell, a part of the phase change layer is filled in the gap between two adjacent heat-conducting fins, and another part is filled in the gap between the heat-conducting fins and the main shell;
[0020] The distance between two adjacent heat-conducting fins is L1, the distance between the heat-conducting fins and the inner wall surface of the main shell is L2, 1.3mm≤L1≤1.8mm, 3mm≤L2≤6mm.
[0021] In some embodiments, the heat storage unit further includes a heat exchange tube, the heat conductive fin has a heat conductive hole, the heat exchange tube is penetrated by a plurality of heat conductive holes of the heat conductive fin, and an end portion extends out of the heat storage housing, and the main housing, the plurality of heat conductive fins and the heat exchange tube define the heat storage space;
[0022] The phase change layer is filled in the heat storage space and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
[0023] In a second aspect, the present application provides an assembly method of a heat storage unit, comprising: mixing the components of the inorganic salt phase change material as described above, and filling the components into the heat storage space of the heat storage shell, wherein the inorganic salt phase change material forms the phase change layer.
[0024] In some embodiments, mixing the components of the inorganic salt phase change material comprises the following steps:
[0025] The components of the polysaccharide are uniformly mixed and premixed to obtain a thickener;
[0026] The inorganic hydrated salt A, the nucleating agent, the thickener and the thermal conductive filler are uniformly mixed and blended to obtain a mixture A;
[0027] The mixture A is heated to a preset temperature, the preset temperature being greater than the melting point of the inorganic hydrated salt A, and subjected to a heating treatment to obtain a molten mixture B;
[0028] The assembly method further includes: filling the molten mixture B into the heat storage space inside the heat storage shell, and cooling and solidifying the molten mixture B to form the phase change layer.
[0029] In some embodiments, the blending process includes:
[0030] Providing the inorganic hydrated salt A, and uniformly mixing the inorganic hydrated salt A, the nucleating agent, the thickener and the thermal conductive filler to obtain a mixture A; or,
[0031] According to the molar ratio of the inorganic salt to the deionized water in the inorganic hydrated salt A, provide an inorganic salt and deionized water, mix the inorganic salt, the nucleating agent, the thickener and the thermal conductive filler evenly, then add deionized water and mix evenly to obtain a mixture A, wherein the temperature of the deionized water is 40°C to 50°C.
[0032] In some embodiments, the heating treatment at least includes: a stirring speed of 40 r / min to 80 r / min, a time of 2 h to 3 h, and a preset temperature greater than the melting point of the inorganic hydrated salt A in the temperature range of 10° C. to 15° C.
[0033] In a third aspect, the present application provides a heat pump system, comprising:
[0034] A heat source, used to provide heat; and
[0035] As described above, the inorganic salt phase change material of the heat storage unit is used to obtain the heat provided by the heat source to perform phase change energy storage.
[0036] Based on the heat storage unit and its assembly method and heat pump system of the embodiments of the present application, by selecting the various components in the inorganic salt phase change material within a suitable range, it is possible to directly mix the various components in the inorganic salt phase change material and then heat them together to above the melting point of the inorganic hydrated salt A. The mixture after the components are melted has a lower viscosity, which is convenient for filling the molten mixture into the small gap of the container, and is easy to fill. In addition, the various components of the inorganic salt phase change material can be melted at a suitable temperature after mixing, and the various components in the molten mixture can maintain good stability at the melting temperature and are not easy to fail, so that they can still play their respective roles during the repeated melting and crystallization of the inorganic salt phase change material. BRIEF DESCRIPTION OF THE DRAWINGS
[0037] In order to more clearly illustrate the embodiments of the present application or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present application. For those skilled in the art, other drawings can be obtained based on these drawings without paying any creative work.
[0038] Figure 1 This is a schematic structural diagram of a heat pump system according to an embodiment of the present application;
[0039] Figure 2 This is a method for preparing an inorganic salt phase change material according to an embodiment of the present application.
[0040] Reference numerals:
[0041] 10. Heat pump system;
[0042] 100. heat storage unit; 110. heat storage housing;
[0043] 200, heat exchange tube; 210, first heat exchange tube; 220, second heat exchange tube;
[0044] 300, heat source; 310, outlet end; 320, inlet end; 400, heating unit;
[0045] 500, reversing valve; 510, first reversing valve; 520, second reversing valve;
[0046] 610. Municipal water source; 620. Domestic water pipe. DETAILED DESCRIPTION
[0047] The endpoints and any values of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values should be understood to include values close to these ranges or values. For numerical ranges, the endpoint values of each range, the endpoint values of each range and the individual point values, and the individual point values can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.
[0048] It should be noted that, in various aspects of the present application, for the same components in various aspects, the present application only describes one aspect once without repeating the description, which should not be understood by those skilled in the art as a limitation to the present application.
[0049] In the present application, unless otherwise stated, the room temperature or normal temperature refers to 25±2°C.
[0050] The present application provides an inorganic salt phase change material composition. The inorganic salt phase change material composition can be used to prepare an inorganic salt phase change material. The inorganic salt phase change material can be applied to a heat pump system to store and release heat.
[0051] The present application provides a heat storage unit, which is used in a heat pump system. The heat storage unit includes a heat storage shell and a phase change layer. The heat storage shell has a heat storage space inside, and the phase change layer is filled in the heat storage space. The phase change layer includes an inorganic salt phase change material, and the inorganic salt phase change material is used to exchange heat with a material in the heat storage space to perform phase change energy storage.
[0052] The inorganic salt phase change material of the embodiment of the present application includes the following components:
[0053] Inorganic hydrated salt A 90.0wt.%~95.0wt.%, nucleating agent 1.0wt.%~5.0wt.%, thickener 0.5wt.%~1.5wt.%, thermal conductive filler 1.0wt.%~3.0wt.%, the thickener includes polysaccharide A and polysaccharide B, polysaccharide A is a linear structure polysaccharide thickener, and polysaccharide B is a network structure polysaccharide thickener.
[0054] In the present application, inorganic hydrated salt A is the main component of the inorganic salt phase change material that undergoes phase change, and the nucleating agent is used to provide nucleation sites for inorganic hydrated salt A, so that the inorganic salt phase change material can be repeatedly melted-crystallized, and then phase change energy storage. The thermal conductivity of inorganic hydrated salt A is relatively poor, and the inorganic salt phase change material is selected to also include a thermal conductive filler, which has good thermal conductivity and is used to improve the overall thermal conductivity of the inorganic salt phase change material to improve the heat transfer efficiency of the inorganic salt phase change material. Due to the disadvantage of phase separation in inorganic hydrated salt A, a thickener is used to increase the overall viscosity of the inorganic salt phase change material. The thickener can capture water molecules and prevent water molecules from escaping from the inorganic salt to inhibit the phase separation of the inorganic salt phase change material, so that the inorganic salt phase change material has good stability during frequent phase changes.
[0055] In order to ensure the thickening effect, a thickener with a relatively high concentration is usually selected in the phase change material system. A high concentration of thickener can make the phase change material have a high viscosity. However, during the dissolution process, it is easy to agglomerate and difficult to disperse evenly. In addition, the high viscosity of the phase change material system is not convenient for filling and bubbles are prone to appear. During the mixing process, the viscosity of the phase change material system can be reduced by increasing the temperature of the system, which can improve the above defects. However, too high a temperature can easily cause the components in the phase change material system to fail, which in turn causes the phase change energy storage capacity of the phase change material to deteriorate.
[0056] The present application selects thickeners including polysaccharides A and polysaccharides B, wherein polysaccharide A includes at least one of straight-chain polysaccharides and polysaccharide B includes at least one of branched polysaccharides. Polysaccharide A serves as the main thickener and polysaccharide B serves as a thickening synergist. The straight-chain polysaccharide A is swollen and interspersed with the branched polysaccharide B, so that the thickener entanglement effect is more sufficient, and covalent bonds are formed between the two to interact with each other, so that the two have a synergistic effect and can have a higher viscosity at a low concentration. The inorganic salt phase change material of the present application can meet the viscosity requirements with a smaller amount of thickener, thereby reducing the amount of thickener used, facilitating the uniform dispersion of the thickener and preventing agglomeration.
[0057] In the present application, the components in the inorganic salt phase change material are selected to be within a suitable range, and based on the total weight of the thickener, the weight percentage of the polysaccharide B is b, 2.9≤a / b≤5.5, and the ratio of the polysaccharide A to the polysaccharide B is appropriate, so that the components in the inorganic salt phase change material can be directly mixed and then heated together to above the melting point of the inorganic hydrated salt A, and the mixture after the components are melted has a lower viscosity, which is convenient for filling the molten mixture into the small gap of the container and dispersing it evenly in the container. In addition, the components of the inorganic salt phase change material can be melted at a suitable temperature after mixing, and the components in the molten mixture can maintain good stability at the melting temperature and are not easy to fail, so that they can still play their respective roles in the process of repeated melting and crystallization of the inorganic salt phase change material.
[0058] When the weight percentage of inorganic hydrated salt A is lower than the lower limit of 90.0wt.%, the specific gravity of inorganic hydrated salt A is low, and the latent heat of phase change decays significantly. When the weight percentage of inorganic hydrated salt A is higher than the upper limit of 95.0wt.%, the water precipitated from inorganic hydrated salt A in the molten state increases, which easily leads to less thickener dosage and reduced thickening effect. When the weight percentage of thickener is lower than the lower limit of 0.5wt.%, the thickener content is insufficient, the thickening effect is poor and phase separation occurs. When the weight percentage of thickener is higher than the upper limit of 1.5wt.%, the thickener content is too large, the viscosity rises sharply and is not conducive to filling.
[0059] In some embodiments, based on the total weight of the thickener, the weight percentage of polysaccharide A is a, 70.0wt.%≤a≤85wt.%, so that after the components of the inorganic salt phase change material are mixed, polysaccharide A penetrates into the network structure of polysaccharide B in a chain structure during the swelling process, so that the structures of polysaccharides A and polysaccharides B are more fully entangled, and it can also prevent a part of the thickener from swelling and then covering other unswollen thickeners, so that the thickener swells more fully.
[0060] In some embodiments, 15 wt.%≤b≤30 wt.%, the amount of polysaccharide B is appropriate, and can provide space for the linear polysaccharide A to insert, providing a thickening network to increase the viscosity.
[0061] In some embodiments, the weight ratio of the inorganic hydrated salt A to the thickener is S, and S satisfies 70.8≤S≤153.3. Within this ratio range, the thickener can be combined with the inorganic hydrated salt A with a small amount of thickener, so that the mixture of the components of the inorganic salt phase change material after melting has a high viscosity sufficient to inhibit phase separation, and the prepared inorganic salt phase change material can also have a certain fluidity, which is sufficient to flow into small gaps without clogging.
[0062] In some embodiments, the polysaccharide A is selected from at least one of sodium carboxymethyl cellulose, sodium hydroxymethyl cellulose, and carboxyethyl cellulose.
[0063] In some embodiments, the polysaccharide B is selected from at least one of xanthan gum, gum arabic, sodium alginate, and chitosan.
[0064] In some embodiments, the inorganic hydrated salt A is selected from at least one of calcium nitrate hexahydrate (Ca(NO3)2·6H2O), sodium thiosulfate pentahydrate (Na2S2O3·5H2O), sodium acetate trihydrate (CH3COONa·3H2O), and calcium chloride hexahydrate (CaCl2·6H2O). By selecting the above inorganic hydrated salt A, during the melting process of the inorganic hydrated salt A, the crystal water will precipitate in the form of free water. When the thickener absorbs the free water, it will swell sufficiently to achieve the thickening effect.
[0065] The melting point Tm of the inorganic hydrated salt A is the basis for the phase change temperature of the inorganic salt phase change material. In the embodiments of the present application, the phase change temperature of the inorganic salt phase change material is approximate to the melting point Tm of the inorganic hydrated salt A. In some embodiments, by selecting the inorganic hydrated salt A with a melting point Tm of 35°C ≤ Tm ≤ 75°C, it can cooperate with the thickener, so that the phase change temperature of the obtained inorganic salt phase change material can not only meet the temperature requirements of domestic water, but also, during the preparation of the inorganic salt phase change material, select an appropriate heating temperature to make the components of the inorganic salt phase change material have an appropriate viscosity for filling after melting, and can also maintain the effectiveness of the components in the inorganic salt phase change material to prevent the components in the inorganic salt phase change material from failing.
[0066] In some embodiments, when Tm satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, the inorganic hydrated salt A is selected from at least one of sodium acetate trihydrate, magnesium nitrate hexahydrate, and potassium acetate monohydrate.
[0067] In some embodiments, when Tm satisfies the conditional formula 35°C < Tm ≤ 50°C, the inorganic hydrated salt A is selected from at least one of sodium thiosulfate pentahydrate, sodium sulfate decahydrate, calcium nitrate hexahydrate, and magnesium sulfate pentahydrate.
[0068] In some embodiments, the nucleating agent is selected from at least one of sodium salts and strontium salts. Among them, the sodium salt of the nucleating agent is selected from at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, and sodium metasilicate nonahydrate, and the strontium salt of the nucleating agent is selected from at least one of strontium chloride hexahydrate (SrCl2·6H2O), strontium carbonate, and strontium sulfate. By selecting the above nucleating agent, crystal nucleation sites can be provided for the inorganic hydrated salt A, so that the inorganic salt phase change material can repeatedly melt-crystallize, and the phase change stability is better.
[0069] Among them, when the nucleating agent is selected from disodium hydrogen phosphate dodecahydrate (Na2HPO4·12H2O), sodium pyrophosphate (Na4P2O7) and other nucleating agents, the nucleating agent can generate crystal nuclei during the crystallization process, thereby providing crystallization sites for the inorganic hydrated salt A and also improving the crystallization rate.
[0070] The thermal conductive filler is selected from at least one of fumed silica, copper foam, expanded graphite, carbon nanotubes, molybdenum disulfide, and boron nitride. In the embodiment of the present application, the thermal conductive filler is selected from insoluble matter and exists as insoluble particles in the inorganic salt phase change material. The particle size Dv of the thermal conductive filler is 50 Meet 300μm≤Dv 50 ≤400μm. Within this particle size range, the components in the inorganic salt phase change material are evenly dispersed and have good stability, which prevents the local sedimentation of the thermal conductive filler, and the thermal conductive filler can play a more uniform and efficient thermal conductive role.
[0071] The heat storage shell includes a main shell and a plurality of heat-conducting fins, wherein the plurality of heat-conducting fins are arranged in the internal space of the main shell, wherein a part of the inorganic salt phase change material is filled in the gap between two adjacent heat-conducting fins, and another part is filled in the gap between the heat-conducting fin and the main shell. Among them, the spacing between two adjacent heat-conducting fins is L1, and the spacing between the heat-conducting fin and the inner wall surface of the main shell is L2, 1.3mm≤L1≤1.8mm, 3.0mm≤L2≤6.0mm, and within this spacing range, the components of the molten inorganic salt phase change material can smoothly enter the heat storage shell, and evenly enter the gap between two adjacent heat-conducting fins and the gap between the heat-conducting fin and the main shell, thereby preventing the generation of bubbles.
[0072] The heat storage unit also includes a heat exchange tube, the heat conduction fin has a heat conduction hole, the heat exchange tube is provided with a plurality of heat conduction holes of the heat conduction fin, and the end of the heat exchange tube extends out of the heat storage shell, and the main shell, the plurality of heat conduction fins and the heat exchange tube define a heat storage space. The inorganic salt phase change material is filled in the heat storage space and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube, and is connected to the heat exchange tube through a plurality of heat conduction fins. The heat exchange tube can also exchange heat with the inorganic salt phase change material through the heat conduction fins, thereby increasing the heat exchange area and improving the heat exchange efficiency.
[0073] The heat exchange tube includes an inlet section, an intermediate section and an outlet section connected in sequence, the intermediate section is arranged in the heat storage space, and the inlet section and the outlet section extend out of the heat storage shell from the heat storage space. The inorganic salt phase change material is filled in the heat storage space and coated on the intermediate section of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube. The heat exchange tube is used to connect with other structures of the heat pump system to transport the heat exchange medium. The number of heat exchange tubes of the heat storage unit can be multiple, so that the heat storage unit can be connected with multiple structural parts of the heat pump system for heat exchange.
[0074] like Figure 1As shown, it is a structural schematic diagram of a heat pump system 10 according to an embodiment of the present application. The heat pump system 10 also includes a heat source 300, which is used to provide heat. The heat source 300 is connected to at least one of the heat exchange tubes 200 of the heat storage unit 100, so that the heat provided by the heat source 300 can be supplied to at least one of the heat exchange tubes 200, and then transferred to the inorganic hydrated phase change material of the phase change layer 20 for heat storage.
[0075] For example, Figure 1 In the heat exchange tube 200, there are two, one of which is the first heat exchange tube 210 and the other is the second heat exchange tube 220. The inlet section of the first heat exchange tube 210 is connected to the outlet end 310 of the heat source 300, and the outlet section is connected to the inlet end 320 of the heat source 300. The inlet section of the second heat exchange tube 220 is connected to the municipal water source 610, and the outlet section is connected to the domestic water pipe 620. The heat storage unit 100 has a heat storage mode, a heat release mode and a mixed mode. Specifically, in the heat storage mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210, and the inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and stores the heat. The high-temperature heat exchange medium becomes a low-temperature heat exchange medium and flows back from the outlet section of the first heat exchange tube 210 to the inlet end 320 of the heat source 300; in the heat release mode, the low-temperature water flow supplied by the municipal water source 610 flows from the second heat exchange tube 210 to the inlet end 320 of the heat source 300. The inlet section of 220 enters the second heat exchange tube 220, and the inorganic hydrated salt A transfers heat to the low-temperature water flow in the second heat exchange tube 220. The low-temperature water flow absorbs heat and becomes high-temperature water flow, and flows out from the outlet section of the second heat exchange tube 220 for supply to users. In the mixed mode, the high-temperature heat exchange medium of the heat source 300 enters the first heat exchange tube 210 from the inlet section of the first heat exchange tube 210. At the same time, the low-temperature water flow supplied by the municipal water source 610 enters the second heat exchange tube 220 from the inlet section of the second heat exchange tube 220. The inorganic salt phase change material absorbs the heat of the high-temperature heat exchange medium in the first heat exchange tube 210 and transfers the heat to the low-temperature water flow in the second heat exchange tube 220 at the same time. The low-temperature water flow absorbs heat and becomes high-temperature water flow or medium-temperature water flow, and flows out from the outlet section of the second heat exchange tube 220 for supply to users.
[0076] The first heat exchange tube 210 and the second heat exchange tube 220 can be made of stainless steel independently. When the inorganic salt phase change material 20 also includes a corrosion inhibitor, the first heat exchange tube 210 and the second heat exchange tube 220 can also include copper material.
[0077] The heat pump system 10 also includes a heating unit 400, a reversing valve 500 and connecting pipes connecting the various structures. The reversing valve 500 includes a first reversing valve 510. The first end of the first reversing valve 510 is connected to the outlet end 310 of the heat source 300, the second end is connected to the heating unit 400, and the third end is connected to the heat exchange pipe 200 of the heat storage unit 100. By switching the flow path of the first reversing valve 510, the outlet end 310 of the heat source 300 can be connected to at least one of the heating unit 400 and the heat storage unit 100 to provide high-temperature heat exchange medium to the heating unit 400 and the heat storage unit 100 accordingly. The number of heating units 400 may be multiple, and the reversing valve 500 may also include a second reversing valve 520. The second reversing valve 520 is arranged on the second end of the first reversing valve 510 and is connected to a connecting pipe connected to the multiple heating units 400. By switching the flow path of the second reversing valve 520, the second end of the first reversing valve 510 is connected to one or more of the multiple heating units 400, and then the heat source 300 is connected to one or more of the multiple heating units 400.
[0078] The present application also provides a method for assembling a heat storage unit, such as Figure 2 As shown, the assembly method includes:
[0079] Step S1, mixing the components of the above inorganic salt phase change material.
[0080] Step S2: Fill the mixed components of the inorganic salt phase change material into the heat storage space inside the heat storage shell.
[0081] Figure 2 In step S1, mixing the components of the inorganic salt phase change material comprises the following steps:
[0082] Step S110: uniformly mix the components of the polysaccharide and perform premixing to obtain a thickener.
[0083] Step S120, uniformly mix the inorganic hydrated salt A, the nucleating agent, the thickener and the thermal conductive filler, and perform a blending process to obtain a mixture A.
[0084] Step S130, heating the mixture A to a preset temperature, which is greater than the melting point of the inorganic hydrated salt A, and performing a heating treatment to obtain a molten mixture B.
[0085] Step S2 includes: filling the melted mixture B in step S130 into the heat storage space inside the heat storage shell, and the melted mixture B is cooled and solidified to form a phase change layer.
[0086] In the embodiments of the present application, after the components of the inorganic salt phase change material are mixed uniformly together, they are heated to the molten state together, and then filled into the heat storage space inside the heat storage shell together. There is no need to add the components in multiple times. The method is simple, and the components mixed together can also be dispersed evenly. The inorganic salt phase change material has good stability during both heat storage and heat release processes. Among them, by adopting the method of pre-mixing the components of the thickener, the polysaccharides of the thickener can be mixed more uniformly, so that after the thickener swells, the intermolecular forces of the polysaccharides can be more sufficient, which helps to further improve the viscosity of the thickener and better improve phase separation.
[0087] In some embodiments, the blending treatment in step S120 includes: directly providing inorganic hydrated salt A, and mixing inorganic hydrated salt A, a nucleating agent, a thickener, and a heat conductive filler uniformly to obtain mixture A.
[0088] Alternatively, the blending treatment in step S120 includes: providing inorganic salts and deionized water according to the molar ratio of the inorganic salts to deionized water in inorganic hydrated salt A. After mixing the inorganic salts, a nucleating agent, a thickener, and a heat conductive filler uniformly, deionized water is added and mixed uniformly to obtain mixture A, where the temperature of the deionized water is 40°C to 50°C. Selecting deionized water at a lower temperature can prevent partial gelatinization of some polysaccharides in the thickener during the addition of deionized water, which affects the swelling of the thickener during subsequent heat treatment. Moreover, mixing in a low-temperature environment can make the components in mixture A mix more uniformly.
[0089] In some embodiments, the heat treatment in step S130 at least includes: the stirring speed is 40 r / min to 80 r / min, the time is 2 h to 3 h, and the preset temperature range greater than the melting point Tm of inorganic hydrated salt A is 10°C to 15°C, so that inorganic hydrated salt A can be fully melted, and at this preset temperature, the nucleating agent can be dispersed evenly, and the thickener can also swell more fully, so that the obtained molten mixture B has an appropriate viscosity, and the components in the molten mixture B can still maintain their effectiveness. Thus, when the molten mixture B solidifies to form an inorganic salt phase change material, the inorganic salt phase change material can perform phase change energy storage.
[0090] When the melting point Tm of inorganic hydrated salt A satisfies the conditional formula 50°C ≤ Tm ≤ 65°C, correspondingly, the preset temperature in the heat treatment is 60°C to 75°C, and the time is 2 h to 3 h; when the melting point Tm of inorganic hydrated salt A satisfies the conditional formula 35°C < Tm ≤ 50°C, correspondingly, the preset temperature in the heat treatment is 50°C to 65°C, and the time is 1.5 h to 2 h.
[0091] In some embodiments, when the heat conductive filler is selected as an insoluble substance, the heat conductive filler is pulverized and then mixed with other components. The particle size Dv of the pulverized heat conductive filler50 Meet 300μm≤Dv 50 ≤400 μm, so that the thermal conductive filler can be evenly dispersed in the premixed liquid. The pulverization process can be carried out by at least one of a ball mill and a high-speed pulverizer.
[0092] The following is a method for preparing an inorganic salt phase change material in combination with examples and comparative examples. Those skilled in the art will understand that the preparation method described in this application is only an example, and any other suitable preparation method is within the scope of this application. In the following examples, unless otherwise specified, all raw materials used are commercially available.
[0093] In each embodiment and comparative example of the present application, the performance test method of the inorganic salt phase change material is as follows:
[0094] 1. Phase change temperature and supercooling test method
[0095] The phase change temperature adopts the step cooling curve method: 100g of phase change material is placed in a high borosilicate glass bottle, a K-type thermocouple is inserted into the middle of the phase change material, and then the phase change material is heated to 20°C above the melting point of inorganic hydrated salt A and stabilized for 30 minutes. Then it is placed in an environment 30°C below the melting point for natural cooling, and the temperature information of the phase change material changing with time is collected to obtain the temperature-time curve and the corresponding theoretical phase change temperature (T theory ) and the actual phase transition temperature (T actual ).
[0096] Theoretical phase transition temperature (T theory ) and the actual phase transition temperature (T actual ) is the supercooling degree (T sc ).
[0097] 2. Test method for latent heat decay rate of phase change after 2000 cycles
[0098] The initial unit mass phase change latent heat (thermal enthalpy) of the phase change material is measured by DSC equipment.
[0099] The phase change material is loaded into the cycle test device.
[0100] The melt-crystallization cycle is carried out as follows:
[0101] (1) Initial temperature 0°C, let stand for 5 minutes;
[0102] (2) Perform heating treatment at a heating rate of 5°C / min, a stop temperature of 80°C, and stand for 5 min;
[0103] (3) Cooling treatment was performed at a cooling rate of 5°C / min, an end temperature of 0°C, and the mixture was allowed to stand for 1 min.
[0104] Among them, the above steps (1)-(3) are the first melt-crystallization cycle, and then the steps (2)-(3) are a melt-crystallization cycle. After the phase change material has been melt-crystallized for 2000 times, the unit mass phase change latent heat of the phase change material after 2000 cycles is measured by DSC equipment.
[0105] The calculation formula of the unit mass phase change latent heat decay rate is: H% = (1-△H n / △H0)×100%;
[0106] Among them, △H n is the latent heat per unit mass of phase change material after n cycles, kJ / kg;
[0107] △H0 is the initial unit mass phase change latent heat of the phase change material, kJ / kg.
[0108] 3. Energy storage density test method
[0109] The density of phase change materials was measured by density meter. s ) and liquid density (р l );
[0110] The solid-state specific heat capacity C of phase change materials was measured by differential scanning calorimetry (DSC) using the MDSC method. ps and liquid specific heat C pl .
[0111] The initial unit mass phase change latent heat ΔH0 of the phase change material was measured by differential scanning calorimetry (DSC).
[0112] The energy storage density △Q is calculated according to the following formula:
[0113] △Q=р s ×(T actual -10)×C ps +(р s +р l ) / 2×△H0+р l× (65-T actual )×C pl .
[0114] 4. Viscosity test method
[0115] (1) The sample to be tested is heated to a preset temperature to melt the sample to be tested.
[0116] (2) Use a rotational viscometer and place the probe of the rotational viscometer in the molten sample to be tested. Adjust the rotor speed to 60 r / min, ensuring that the rotor does not touch the wall or bottom of the sample container when in motion. Wait for the rotational viscometer to stabilize and then record the reading, which is the viscosity of the sample to be tested.
[0117] Example 1-1
[0118] This embodiment provides a method for preparing an inorganic hydrated phase change material, the method comprising the following steps:
[0119] (1) Premixing
[0120] Sodium carboxycellulose, sodium alginate and gum arabic are uniformly mixed in a weight ratio of 8:1:1 to obtain a thickener.
[0121] (2) Blending treatment
[0122] Weigh 55.47g of inorganic salt sodium acetate, 4.6g of nucleating agent disodium hydrogen phosphate dodecahydrate, and particle size Dv 50 3.00 g of 300 μm thermal conductive filler molybdenum disulfide and 0.4 g of thickener were mixed at 15° C., and then 36.53 g of deionized water at 45° C. were added, and the mixture was mixed at a stirring speed of 50 r / min for 0.5 h to obtain a mixture A.
[0123] (3) Heat treatment
[0124] The mixture A was heated to 75° C. and mixed uniformly at a stirring speed of 40 r / min for 2 h to obtain a molten mixture B.
[0125] (4) Cooling treatment
[0126] The molten mixture B is cooled to room temperature 25° C., and the molten mixture B is solidified to form an inorganic salt phase change material.
[0127] The phase change layer of the heat storage unit is formed by cooling the molten mixture B to room temperature 25°C and solidifying it.
[0128] Examples 1-2 to 1-9 and Comparative Examples 1-1 to 1-2 are the same as Example 1-1 except that the contents of inorganic hydrated salt A, nucleating agent, thermal conductive filler and thickener are adjusted as shown in Table 1 in each processing step.
[0129] Example 1-8 is the same as Example 1-1 except that in step (2), the contents of inorganic hydrated salt A, nucleating agent, thermal conductive filler and thickener are adjusted as shown in Table 1, and in step (3), the mixture A is heated to 60° C. The phase transition temperature of sodium thiosulfate pentahydrate is 48.0° C.
[0130] Example 1-9 is the same as Example 1-1 except that in step (2), the contents of inorganic hydrated salt A, nucleating agent, thermal conductive filler and thickener are adjusted as shown in Table 1, and in step (3), the mixture A is heated to 50° C. The phase transition temperature of calcium chloride hexahydrate is 29.0° C.
[0131] Examples 1-10 to 1-15, Comparative Examples 1-3 to 1-4 are the same as Examples 1-3, except that step (1) adjusts the proportions of the components in the thickener as shown in Table 1, and step (2) adjusts the contents of the inorganic hydrated salt A, the nucleating agent, the thermally conductive filler and the thickener as shown in Table 1.
[0132] Example 1-16 is the same as Example 1-3 except that in step (1), thickener 2 is selected as sodium alginate and thickener 3 is selected as soluble starch as shown in Table 1, and in step (2), the contents of nucleating agent, thermal conductive filler and thickener are adjusted as shown in Table 1.
[0133] Example 1-17 is the same as Example 1-3 except that in step (1), thickener 2 is selected as xanthan gum and thickener 3 is chitosan as shown in Table 1, and in step (2), the contents of nucleating agent, thermal conductive filler and thickener are adjusted as shown in Table 1.
[0134] The preparation parameters and performance parameters of Examples 1-1 to 1-9 and Comparative Examples 1-1 to 1-2 are as follows:
[0135] As shown in Table 1.
[0136]
[0137] From the results of Example 1-1 to Example 1-9 and Comparative Example 1-1 to Comparative Example 1-2 in Table 1, it can be seen that by selecting the content of each component in the inorganic salt phase change material composition within a suitable range, the viscosity of the obtained molten mixture B is suitable, which is convenient for filling in a small space, and the phase change latent heat decay rate, supercooling degree and energy storage density of the inorganic salt phase change material after 2000 cycles are all within a suitable range. The inorganic salt phase change material of the embodiment of the present application can be used in a heat pump system and has good heat storage and cold storage performance. Among them, when the weight percentage of the inorganic hydrated salt A is less than 90wt.%, the inorganic hydrated salt A has a low specific gravity, the phase change latent heat decay rate becomes larger, and the phase change latent heat decay is very obvious. When the weight percentage of the inorganic hydrated salt A is higher than 95wt.%, the amount of the inorganic hydrated salt A is too large, which easily leads to too little thickener. After the inorganic salt phase change material is heated and melted, its viscosity is also small, which easily leads to phase separation.
[0138] The preparation parameters and performance parameters of Examples 1-10 to 1-17 and Comparative Examples 1-3 to 1-4 are shown in Table 2.
[0139]
[0140] From the results of Examples 1-10 to 1-17 and Comparative Examples 1-3 to 1-4 in Table 2, it can be seen that the weight percentage of the thickener is selected in the range of 0.5wt.% to 1.5wt.%, the weight ratio S of the inorganic hydrated salt A to the thickener is 70.8≤S≤153.3, and the ratio of the weight percentage a of the polysaccharide A to the weight percentage b of the polysaccharide B is 2.9≤a / b≤5.5, which can make the viscosity of the mixture B in the molten state suitable for filling, and the viscosity of the inorganic salt phase change material in the molten state is suitable, which helps to maintain the phase stability of the inorganic salt phase change material. When the weight percentage of the thickener is lower than 0.5wt.%, the specific gravity of the thickener is low, the thickener content is insufficient, the thickening effect is poor, and phase separation occurs. When the weight percentage of the thickener is higher than 1.5wt.%, the thickener dosage is too large, the viscosity of the mixture B rises sharply, which is not conducive to filling.
[0141] The above description is only a preferred embodiment of the present application and is not intended to limit the present application. Any modifications, equivalent substitutions and improvements made within the spirit and principles of the present application should be included in the protection scope of the present application.
Claims
1. A heat storage unit, characterized in that: Used in a heat pump system, the heat storage unit comprises a heat storage shell and a phase change layer, the heat storage shell has a heat storage space, and the phase change layer is filled in the heat storage space; Wherein, the phase change layer comprises an inorganic salt phase change material, and the inorganic salt phase change material comprises the following components: Inorganic hydrated salt A 90.0wt.%~95.0wt.%, nucleating agent 1.0wt.%~5.0wt.%, thickener 0.5wt.%~1.5wt.%, thermal conductive filler 1.0wt.%~3.0wt.%; The thickener comprises polysaccharide A and polysaccharide B, wherein the polysaccharide A comprises at least one of linear polysaccharides, and the polysaccharide B comprises at least one of branched polysaccharides; Based on the total weight of the thickener, the weight percentage of the polysaccharide A is a, and the weight percentage of the polysaccharide B is b, wherein 2.9≤a / b≤5.
5.
2. The thermal storage unit according to claim 1, characterized in that: 75.0wt.%≤a≤84.6wt.%.
3. The thermal storage unit according to claim 1, characterized in that: The polysaccharide A is selected from at least one of sodium carboxymethyl cellulose, sodium hydroxymethyl cellulose and hydroxyethyl cellulose; The polysaccharide B is selected from at least one of xanthan gum, sodium alginate, pectin and carrageenan.
4. The thermal storage unit according to any one of claims 1 to 3, characterized in that: The weight ratio of the inorganic hydrated salt A to the thickener is S, and S satisfies 70.8≤S≤153.
3.
5. The thermal storage unit according to claim 1, characterized in that: The inorganic hydrated salt A is selected from at least one of magnesium nitrate hexahydrate, sodium thiosulfate pentahydrate, sodium acetate trihydrate, and calcium chloride hexahydrate; The nucleating agent is selected from sodium salts and strontium salts: at least one of disodium hydrogen phosphate dodecahydrate, sodium pyrophosphate, sodium metasilicate nonahydrate, strontium sulfate, and strontium chloride hexahydrate; The thermal conductive filler is selected from at least one of fumed silica, copper foam, expanded graphite, carbon nanotubes, molybdenum disulfide and boron nitride.
6. The thermal storage unit according to claim 1, characterized in that: The heat storage housing comprises: main housing; A plurality of heat-conducting fins are arranged in the inner space of the main shell, a part of the phase change layer is filled in the gap between two adjacent heat-conducting fins, and another part is filled in the gap between the heat-conducting fins and the main shell; The distance between two adjacent heat-conducting fins is L1, the distance between the heat-conducting fins and the inner wall surface of the main shell is L2, 1.3mm≤L1≤1.8mm, 3mm≤L2≤6mm.
7. The thermal storage unit according to claim 6, characterized in that: The heat storage unit further includes a heat exchange tube, the heat conduction fin has a heat conduction hole, the heat exchange tube is penetrated by a plurality of heat conduction holes of the heat conduction fin, and an end of the heat exchange tube extends out of the heat storage shell, and the main shell, the plurality of heat conduction fins and the heat exchange tube define the heat storage space; The phase change layer is filled in the heat storage space and coated on the outer surface of the heat exchange tube to exchange heat with the heat exchange medium in the heat exchange tube.
8. A method for assembling a heat storage unit, characterized in that: include: After the components of the inorganic salt phase change material according to any one of claims 1 to 5 are mixed, the components are filled into the heat storage space of the heat storage shell, and the inorganic salt phase change material forms the phase change layer.
9. The assembly method according to claim 8, characterized in that: Mixing the components of the inorganic salt phase change material comprises the following steps: The components of the polysaccharide are uniformly mixed and premixed to obtain a thickener; The inorganic hydrated salt A, the nucleating agent, the thickener and the thermal conductive filler are uniformly mixed and blended to obtain a mixture A; The mixture A is heated to a preset temperature, the preset temperature being greater than the melting point of the inorganic hydrated salt A, and subjected to a heating treatment to obtain a molten mixture B; The assembling method further includes: filling the molten mixture B into the heat storage space inside the heat storage shell, and cooling and solidifying the molten mixture B to form the phase change layer.
10. The assembly method according to claim 9, characterized in that: The blending process includes: Providing the inorganic hydrated salt A, and uniformly mixing the inorganic hydrated salt A, the nucleating agent, the thickener and the thermal conductive filler to obtain a mixture A; or, According to the molar ratio of the inorganic salt to the deionized water in the inorganic hydrated salt A, provide an inorganic salt and deionized water, mix the inorganic salt, the nucleating agent, the thickener and the thermal conductive filler evenly, then add deionized water and mix evenly to obtain a mixture A, wherein the temperature of the deionized water is 40°C to 50°C.
11. The composition according to claim 9, characterized in that The heating treatment at least includes: a stirring speed of 40 r / min to 80 r / min, a time of 2 h to 3 h, and a temperature range of 10° C. to 15° C. above the melting point of the inorganic hydrated salt A, of the preset temperature.
12. A heat pump system, characterized in that: include: A heat source, used to provide heat; and As in any one of claims 1 to 7 above, the inorganic salt phase change material of the thermal storage unit is used to obtain heat provided by the heat source to perform phase change energy storage.
